The Arab Spring: pathways of repression and reform - Brownlee, Jason (Oxford University Press, 2015)
Several years after the Arab Spring began, democracy remains elusive in the Middle East. The Arab Spring that resides in the popular imagination is one in which a wave of mass mobilization swept the broader Middle East, toppled dictators, and cleared the way for democracy. The reality is that few Arab countries have experienced anything of the sort. While Tunisia made progress towards some type of constitutionally entrenched participatory rule, the other countries that overthrew their rulers - Egypt, Yemen, and Libya - remain mired in authoritarianism and instability. Elsewhere in the Arab world uprisings were suppressed, subsided or never materialized. The Arab Spring's modest harvest cries out for explanation. Why did regime change take place in only four Arab countries and why has democratic change proved so elusive in the countries that made attempts? This book attempts to answer those questions. First, by accounting for the full range of variance: from the absence or failure of uprisings in such places as Algeria and Saudi Arabia at one end to Tunisia's rocky but hopeful transition at the other. Second, by examining the deep historical and structure variables that determined the balance of power between incumbents and opposition. Brownlee, Masoud and Reynolds find that the success of a domestic campaign to oust the ruler was preconditioned by two variables: oil wealth and the precedent of hereditary succession. When rulers were ousted, the balance of power at the time of transition goes far in predicting the character of new constitutional provisions and the trajectory of democratization writ large.